PENGARUH MEDIA SOSIAL TIK TOK TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V UPT SPF SD INPRES BTN IKIP 1 - Hidayah, Nur; Syah, Syahrul; Salsabila, Naila; Faisal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the relationship between TikTok usage and learning outcomes in Pancasila Education among fifth-grade students at UPT SPF SD Inpres BTN IKIP 1. The research addresses concerns about whether social media use affects academic performance. The objective is to determine the existence and magnitude of the influence between TikTok usage and students’ learning outcomes. This study applies a quantitative correlational design. Data were collected using a questionnaire and documentation of student scores. The instrument met validity requirements, with 20 out of 25 items declared valid, and showed high reliability with a Cronbach’s Alpha value of 0.819. Descriptive analysis indicated moderate levels of TikTok usage and relatively high learning outcomes. Normality testing showed non-normal data distribution, so Spearman correlation was used. The results revealed a correlation coefficient of 0.036 with a significance value of 0.861, indicating a very weak and non-significant relationship. Linear regression analysis also showed no significant effect, with a significance value of 0.304 and a coefficient of determination of 0.044, meaning TikTok usage contributed only 4.4 percent to learning outcomes, while 95.6 percent was influenced by other factors. These findings indicate that TikTok usage does not significantly affect students’ academic performance. Learning outcomes are more strongly influenced by internal factors such as motivation and discipline, as well as external factors such as teaching methods and learning environment.